Family structure trajectories and early child health in the UK: Pathways to health. (July 2019) - Panico, Lidia; Bartley, Melanie; Kelly, Yvonne J; McMunn, Anne; Sacker, Amanda
Abstract: A large body of literature has shown marked differences in the average levels of resources and child well-being across different family structures. Studies have examined cognitive, educational and behavioural outcomes; less is known about differentials in physical health, and about dynamics in early childhood. Furthermore, up to the present time, less emphasis has been placed on describing the underlying mechanisms relating childhood experiences of family structure to health. In this paper, we hypothesize that socio-economic characteristics and family structure trajectories will affect every-day, more proximal processes (material, behavioural and family stress pathways) directly experienced by the child, which will in turn affect child health. Using the UK Millennium Cohort Study, a nationally representative cohort of over 19 000 children born in 2001 and living in the UK shortly thereafter, we employ Graphical Chain Models to map the processes linking family structure trajectories to three physical health outcomes at age 5: overweight/obesity, respiratory health, and accidental injury. We construct family trajectories to highlight two components: status (distinguishing between married, cohabiting and single parents), and (in)stability. We show that both status, the (in)stability of that status, and their interplay, are important components of family structure trajectories which correlate to children's early physical health. Analyses highlight the relative importance of distinct pathways across different health outcomes. As well as some outcome-specific paths, we find that "family stress" variables appeared to underscore the relationship between family structure and child physical health, pointing to the importance of such variables in understanding how family structure relates to early child health. Highlights: Family structure trajectories are correlated to early child physical health. Both status (married, cohabiting, single) and instability were important features. We know little about the mechanisms relating family structure to early child health. Family stress appeared to be an important mechanisms across all family trajectories. Housing quality was important for cohabitors; daily routines for separating parents.